EMOTIONAL BURNOUT IN NURSES: DIAGNOSIS AND PREVENTION - Svitlana I. Boitsaniuk; Mariana O. Levkiv; Pavlo Yu. Ostrovskyi (Клінічна та профілактична медицина, 2025)
Introduction. The presence of burnout, anxiety, and depression among health professionals is a crucial issue that must be carefully addressed. The signs of a burnt-out in nurses are not always easy to identify and may be physical, psychological, emotional, and/or behavioral. The article provides a theoretical analysis of the problem of emotional burnout and also concludes that it is one of the central issues in becoming a professional nurse.